Pengaruh Anggaran Biaya Operasional dan Anggaran Pendapatan terhadap Kinerja Keuangan pada Pt. Sinar Mas Smart Tbk - erma novalina; Efni Anita; Agusriandi (Manajemen Keuangan Syariah, 2023)
ABSTRACT The purpose of this study was to analyze the effect of operating expense budget and revenue budget on financial performance at PT Sinar Mas SMART Tbk. This research is a type of quantitative research. The sample uses purposive sampling method, namely the company's Gross Profit Margin (GMP) as well as the operating expense and revenue budgets for the 2015-2021 period. The data were analyzed by multiple linear regression and hypothesis testing using the t-test and R2 test with the help of SPSS 24.0 for windows software. The results showed that: The Operating Cost Budget partially has a significant effect on financial performance, this can be seen from the significance value (P Value) 0.003 which is smaller than 0.05. Budget Revenue partially has a significant effect on financial performance with a significance level (P Value) of 0.006 which is smaller than 0.05. And the contribution value of the coefficient of determination (Adjusted R-Square) of 0. 803 which means that the variation that occurs in the dependent variable (Financial performance) is 80.3% influenced by the independent variable (Operating cost budget and revenue budget) the rest is 19.7% (100% - 80.3%) while the rest is influenced by other factors. Keywords: Operating Expense Budget, Revenue Budget, Financial Performance